5th Aranchyn Readings (Kyzyl, September 14, 2016) - Asonychev, Anton A. (The New Research of Tuva, 2016)
This is a review of one of the most significant academic events in Tuva in the year 2016 – 5th international Aranchyn Readings, which took place in Kyzyl on September 14, 2016. This research conference has been held by Tuva Institute for Humanities and Applied Socioeconomic Studies (TIGPI) in collaboration with the Yu.L. Aranchyn Foundation since 2007. It honors the memory of Yurii Luduzhapovich Aranchyn (1926-1997), Doctor of history, prominent Tuvan scholar, statesman and public person. Since his contribution to research spans a wide range of fields, memorial conferences bring together scholars and scientists of various areas– history, folklore studies, economics, social science and literary studies, as well as public figures. This year’s conference marked a number of anniversaries. On December 21 Yu.L. Aranchyn, a scholar of Tuvan history and 3rd Director of Tuva Research Institute of Language, Literature and History (TNIIYaLI, now TIGPI) would have turned 90. May 9 marks the centenary of writer and TNIIYaLI 2nd Director, Nikolai Alekseyevich Serdobov, Doctor of History, author of the fundamental monograph “Istoriia formirovaniia tuvinskoi natsii” (The History of the Rise of the Tuvan Nation (1971)). Another important date is the 95th anniversary of the foundation of the People’s Republic of Tuva. A number of papers presented at the conference covered various events and aspects of PRT’s history. 5th Aranchyn Readings for the first time in the conference’s history featured international participation. Scholars from Kyrgyzstan, Turkey and Hungary joined their colleagues from various regions of Russia (Republic of Tuva, Republic of Khakassia, Republic of Altai, the cities of Krasnoyarsk and Novosibirsk). Our review also provide excerpts from the conference’s final statement, including the prospects of the development of Tuvan studies.